2014
DOI: 10.1109/tasc.2013.2284722
|View full text |Cite
|
Sign up to set email alerts
|

Canted–Cosine–Theta Magnet (CCT)—A Concept for High Field Accelerator Magnets

Abstract: Canted-Cosine-Theta (CCT) magnet is an accelerator magnet that superposes fields of nested and tilted solenoids that are oppositely canted. The current distribution of any canted layer generates a pure harmonic field as well as a solenoid field that can be cancelled with a similar but oppositely canted layer. The concept places windings within mandrel's ribs and spars that simultaneously intercept and guide Lorentz forces of each turn to prevent stress accumulation. With respect to other designs, the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 13 publications
(7 reference statements)
0
29
0
Order By: Relevance
“…Originally proposed by Meyer and Flasck in 1969 [32], the concept has recently gained interest for various accelerator magnet applications [33][34][35][36][37][38].…”
Section: B a Canted Cos θ Dipole Windingmentioning
confidence: 99%
“…Originally proposed by Meyer and Flasck in 1969 [32], the concept has recently gained interest for various accelerator magnet applications [33][34][35][36][37][38].…”
Section: B a Canted Cos θ Dipole Windingmentioning
confidence: 99%
“…For typical high field accelerator dipoles this angle is between 15 and 30 degrees. The resulting field is very close to a perfect dipole, as described in [25]. A similar approach of simply canting the windings to produce a dipole, when applied in the curved geometry of a gantry magnet, leads to the generation of a "dipole" plus higher order "harmonics" (quadrupole, sexupole, etc.).…”
Section: A Magneticsmentioning
confidence: 69%
“…These studies have shown the feasibility and advantages of using the canted cosine theta (CCT) design [19][20][21][22][23][24][25] to generate desired field multipoles in a large aperture superconducting gantry magnet. Using the CCT approach, a novel magnet concept has been developed to produce the alternating focusing and defocusing fields needed for the achromatic gantry, which is described in detail in Sec.…”
Section: A Combined-function Efficient Alternating-gradient (Agmentioning
confidence: 99%
“…This design, first proposed many years ago [2], [3], has more recently been of interest for reducing Lorentz force induced stress in high field Nb 3 Sn magnets [4]- [6]. This reduction is achieved by introducing a mechanical structure internal to the winding pack to intercept and prevent the accumulation of Lorentz forces on the level of individual turns [7].…”
Section: T He Us Magnet Development Program (Us-mdp) Is Pur-mentioning
confidence: 99%